Storytelling as a creative activity for the development of students’ writing skills in 9th graders. - Pibaque Sánchez, Shirley Katiuska (2023)
Storytelling is a highly effective method for teaching English as a foreign language, as it allows students to engage with the language in a creative and authentic way. However, despite its potential benefits, it is not often use in EFL classrooms. This lack of application may be due to factors such as insufficiency of teacher training and support, emphasis on traditional teaching methods, lack of resources and materials and lack of support from educational systems. To improve the situation, it is important for teachers to receive training in storytelling method, to have access to appropriate materials and resources, and to have support from educational systems in implementing this approach in the classroom. With these steps, students can benefit from the advantages that storytelling has to offer, such as increased engagement and improved communicative skills.